(untitled) (Scientific journal of the Fergana State University, 2024)
The land of Termiz is one of the ancient centers of knowledge of Movarunnahr, like Kesh, Nasaf, Samarkand, Bukhara, Khorezm, Shosh, Fergana, Margilan. This city is mentioned in historical sources with such adjectives as “city of scientists”, “land of great thinkers”, “land of great scholars” and “mother of cities”. Today, the names of more than 200 thinkers who emerged from this foundation are mentioned in historical sources. Mature scholars in the fields of hadith, jurisprudence, speech, logic, geometry, astronomy and literature were educated on this land, and people of the whole world shared knowledge and knowledge. Arshy Termizi, who is considered one of such nobles, carried out scientific and creative activities in India in the 16th and 17th centuries. This article analyzes the thinker’s life, rich literary heritage, and the meaning of poetry. Information about the thinker in historical and modern sources was studied based on the method of literary-source studies and textual studies, and scientific conclusions related to the topic were given. At the end of the article, the direction of activity of the Termizites who worked in India was shown with factual information.